Homotopske grupe v fiziki - Osolnik, Ema (Matrika, 2023)
Many problems in physics can be formulated in the context of homotopy groups. Because of their clean mathematical properties, fundamental groups are especially helpful when it comes to understanding order parameter spaces and thus explaining phase transitions. We often find their applications in systems of condensed and solid matter.
Keywords: condensed matter; fazni prehodi; fundamental groups; fundamentalne grupe; homotopske grupe; homotopy groups; kondenzirane snovi; phase transitions; solid matter; trdne snovi